Prognostic value of heart rate variability in atrial fibrillation recurrence following catheter ablation: A systematic review and meta-analysis - Zhang, Enyuan; Liang, Shuo; Sun, Tianhong; Xu, Jing; Lu, Fengmin; Wu, Dongyan; Zhang, Jingkun; He, Le; Zhang, Fan; Fan, Shaobo; Ma, Wei (Frontiers in Cardiovascular Medicine, 2023)
Background Atrial fibrillation (AF) has been a worldwide health issue with increasing prevalence and mortality. Recently, increasing attention has been gained to the relationship between heart rate variability (HRV) and the clinical prognosis of AF catheter ablation. We aimed to evaluate the prognostic value of HRV in AF recurrence. Methods We systematically searched Web of Science, PubMed, and Embase from inception until 17 August 2022 to conduct the systematic review and meta-analysis. We included the studies reporting the predictive value of HRV parameters for AF recurrence or in which HRV parameters in AF recurrence and non-recurrence groups were individually reported. Results Finally, we enrolled 16 studies, including 2,352 patients. Higher rMSSD could independently predict AF recurrence following catheter ablation (OR: 1.02, 95% CI: 1.00–1.04; p = 0.03). Higher HF (OR: 1.55, 95% CI: 1.05–2.28; p = 0.03) and lower LF/HF (OR: 1.12, 95% CI: 1.03–1.20; p = 0.004) could independently predict AF recurrence within 1 year. Higher SDNN (OR: 1.02, 95% CI: 101–1.02; p = 0.0006) could independently predict AF recurrence among patients with paroxysmal AF. Almost all HRV parameters within 3 days after catheter ablation and lnHF, lnLF, and rMSSD at 3 months after catheter ablation performed significant differences in AF recurrence and non-recurrence groups. Conclusion Heart rate variability, especially higher rMSSD (within short-term and long-term periods), was closely related to recurrent AF following catheter ablation, highlighting the clinical importance of HRV in the prognosis of AF following catheter ablation.